PATH-35. RETROSPECTIVE ANALYSIS OF 145 PATIENTS WITH GLIOBLASTOMA; CORRELATING MOLECULAR ALTERATION INCIDENCE WITH DEMOGRAPHICS, TUMOR LOCATION, AND PROGNOSIS. (11th November 2019) - Lobbous, Mina; Tucker, ZacK; Coffee, Elizabeth; Nabors, Louis
Abstract: Glioblastoma is the most common and most aggressive primary brain tumor in adults. Glioblastoma was the first neoplasm to be systemically studied by The Cancer Genome Atlas and is one of the most molecularly well-characterized tumors in humans. Molecular profiling of glioblastoma is increasingly available and had led to the identifications of multiple prognostic factors as well as potential actionable targets for novel therapies. We identified 145 patients diagnosed with glioblastoma whose tumor tissue was analyzed using next generation sequencing (NGS). The NGS was performed using validated, commercially available panels. We studied somatic genetic alterations with a particular focus on TERT (which was altered in 55.9% of patients in the dataset), CDKN2A (44%), TP53 (39%), EGFR (38.6%), PTEN (31%), IDH1 (20%), and CDK4 (9%). These molecular alterations were analyzed in relation to the patients' tumor locations, demographics, and outcomes. We used multiple binary logistic regressions to assess whether demographics and tumor location were predictive of the above alterations We also assessed the relationship between molecular alterations and outcomes when controlling for treatment and demographic variables. Among demographic variables, age predicted alterations in IDH1, EGFR, TERT, TP53, and PTEN. Frontal lobe tumors were more likely to be IDH1-mutated, irrespective of patient age. Sex and race did not predict the incidence of the molecular alterations of interest. Analysis of outcomes revealed that, when controlling for treatment and demographic variables, TERT promoter mutations, TP53 nonsense mutations, and EGFR A289V were predictive of a decreased progression-free survival, while CDKN2A deletion, PTEN missense mutations, and EGFR A289V were predictive of decreased overall survival. Our experience highlights the importance of incorporating routine NGS in the management of patients with glioblastoma. More studies are required to evaluate the predictive and/or prognostic values of different molecular alterations.